2016
DOI: 10.1038/srep30165
|View full text |Cite
|
Sign up to set email alerts
|

Bystander autophagy mediated by radiation-induced exosomal miR-7-5p in non-targeted human bronchial epithelial cells

Abstract: Radiation-induced bystander effect (RIBE) describes a set of biological effects in non-targeted cells that receive bystander signals from the irradiated cells. RIBE brings potential hazards to adjacent normal tissues in radiotherapy, and imparts a higher risk than previously thought. Excessive release of some substances from irradiated cells into extracellular microenvironment has a deleterious effect. For example, cytokines and reactive oxygen species have been confirmed to be involved in RIBE process via ext… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
77
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 67 publications
(80 citation statements)
references
References 55 publications
(70 reference statements)
3
77
0
Order By: Relevance
“…One other miRNA, miR-7, is noteworthy because it has previously been detected in exosomes derived from irradiated bronchial epithelial cells and linked directly to propagation of radiation-induced bystander effect in recipient cells (Song et al, 2016). Autophagy induced by exosomal miR-7-5p was associated with EGFR/Akt/mTOR signaling pathway.…”
Section: Discussionmentioning
confidence: 98%
“…One other miRNA, miR-7, is noteworthy because it has previously been detected in exosomes derived from irradiated bronchial epithelial cells and linked directly to propagation of radiation-induced bystander effect in recipient cells (Song et al, 2016). Autophagy induced by exosomal miR-7-5p was associated with EGFR/Akt/mTOR signaling pathway.…”
Section: Discussionmentioning
confidence: 98%
“…These results may be interpreted that MEG3 acted as a sponge of miR-7-5p to regulate the activation of downstream mTOR signalling, and in turn, modulate cardiomyocytes autophagy. MiR-7-5P is an important regulator in cell autophagy in various cell type [55][56][57].…”
Section: Discussionmentioning
confidence: 99%
“…We and other colleagues have shown that the increase in basal autophagy accompanies the development of cisplatin resistance in NSCLC cells and that inhibiting basal autophagy sensitizes NSCLC cells to cisplatin-induced apoptosis (17)(18)(19). In addition, previous studies show that exosomal miRNAs are able to regulate autophagy in recipient cells by targeting autophagyrelated genes (20)(21)(22). These findings have driven us to investigate the prognostically relevant correlation between basal autophagy contributing to treatment responsiveness and miRNAs derived from circulating exosomes in patients with NSCLC.…”
Section: Introductionmentioning
confidence: 94%